Virtue: the missing piece in spiritual leadership - McGhee, P; Grant, P (Australian Association of Professional and Applied Ethics, 2009)
Fry’s (2003, 2008) models of spiritual leadership have successfully shown that spiritual leaders can create greater organisational commitment, productivity and improved employee well-being. In particular, they have proved beneficial to organisations such as the army and the police. This paper explains the origins of spiritual leadership and Fry’s model in particular and builds on this model using Aristotle’s theory of virtue. Fry’s model has been criticised for a number of reasons including instrumentalising spirituality and for not explaining how leaders and followers become spiritual. The main thrust of this paper is to modify Fry’s Spiritual Leadership model by replacing values with the Aristotelian notion of virtue. This revised framework offers an improved understanding of spiritual leadership and provides potential outcomes that are of significant benefit to law-enforcing entities.